Immunometabolism in rheumatoid arthritis. Issue 3 (3rd July 2018) - Okano, Takaichi; Saegusa, Jun; Takahashi, Soshi; Ueda, Yo; Morinobu, Akio
Abstract: Recent studies have revealed a relationship between cellular metabolism and cell function in immune cells. Cellular metabolism not only provides supplemental ATP, but also supports dynamic changes in cell proliferation and differentiation. For example, T cells exhibit subset-specific metabolic profiles, and require certain types of metabolism for their functions. Determining the metabolic profiles that support inflammatory immune responses may lead to novel treatment strategies for chronic inflammatory diseases such as rheumatoid arthritis (RA). However, the mechanisms by which metabolism modulates cell function have been unclear. Recent studies have begun to unveil unexpected non-metabolic functions for metabolic enzymes in the context of inflammation, including roles in signaling and gene regulation. Here we describe recent findings related to immunometabolism, the metabolome of RA patients, and the metabolically independent functions of glycolytic enzymes. We discuss how metabolic processes impact immune cells, especially T cells and fibroblast like synoviocytes, which are considered the orchestrators of autoimmune arthritis.